Diagnostic hysteroscopy. Essalud's South East National Hospital - Ávila Alatrista, José (2015)
Objectives: To determine the usefulness of hysteroscopy in the diagnosis of endometrial pathology as well as the relation among hysteroscopy, ultrasound and Pathology. Design: Descriptive, observational, retrospective study. Material and Methods: Between April 2000 and June 2002, 130 cases of diagnostic hysteroscopy were performed. In order to determine the coincidence among diagnostic methods, Kappa test was used for non-parametric variables, considering excellent concordance values above 0, 70, acceptable between 0,40 and 0, 70, and defficient below 0,40. Result: We found a high reliability of ultrasound in relation to hysteroscopy but the Kappa index for both methods was deficient. There was good correlation of hysteroscopy and pathology with acceptable kappa index and excellent kappa index for submucous myomas, endometrial polyps and endometrial hyperplasia. Conclusions: Notwithstanding direct vision of the endometrial cavity by hysteroscopy, false positive and false negative results were important. Diagnosis with this method must be presumptive and will need pathology confirmation.